The Outcome of Corrective Transverse Osteotomy in Paediatric Tibia Vara - IRWAN, MOHAMAD ALI; Chan, Wai Hoong; Mohd Anuar Ramdhan, Ibrahim; Faris Indra Prahasta, Didi Indra (Jaypee Brothers Medical Publishers (P) Ltd, 2024)
Abstract Background: Tibia vara is a three-dimensional deformity of the proximal tibia, varus, internal tibial torsion and procurvatum. It is an uncommon deformity with the surgical management varied. This study describes the outcomes of tibia vara management using a corrective transverse osteotomy in one centre. Materials and methods: A retrospective cohort study was conducted involving eight patients with tibia vara (ten tibias). Consent was obtained for treatment using an acute corrective osteotomy. Measurements of Drennan’s angle, the tibiofemoral angle (TFA) and the procurvatum angle were measured preoperatively and postoperatively both just after surgery and at 1 year. A validated questionnaire—the Knee Outcome Survey of Activity Daily Living (KOS-ADL)—was utilised to assess clinical function and outcome. Also recorded were the intraoperative and postoperative complications, the radiological lower limb alignments, the union rate and the recurrence of deformity. Results: There were eight patients involved in this study with a total of ten tibias (six with unilateral tibias and two with bilateral tibias). The mean age of the patients was 11.3 years old (ranging from 8 to 15 years old) with most males (five males and three females). The affected tibias were 6 right sided and 4 left sided. Measurements of Drennan’s angle, the TFA and the procurvatum angle were used to determine lower limb alignment preoperatively, postoperatively (immediate post-surgery) and at 1-year follow-up. Functional parameters were measured using the KOS-ADL. A descriptive analysis between the preoperative and postoperative variables was done. The mean for Drennan’s angle was 21.6 (±5.2) preoperatively, 3.6 (± 2.3) postoperatively and 4.9 (±2.8) at 1-year follow-up. The TFA was improved from 22.6 (±6.1) preoperatively to 3.5 (±2.8) postoperatively and 4.4 (±2.0) at 1-year follow-up. The procurvatum angle was improved preoperatively from 8.20 (±7.5) to 2.40 (±2.5) postoperatively and 2.20 (±2.5) at 1-year follow-up. At the latest follow-up, the ADLS mean score was 98.5 (±2.6) while the SAS mean score was 97.5 (±3.3). The mean length follow-up period was 2 years (ranging from 1 year to 3 years). None of the patients developed postoperative complications with all achieving union without deformity recurrence in the period of observation. Conclusion: This study revealed that acute correction via a corrective transverse osteotomy of the tibia is a safe and effective method in treating tibia vara. Keywords: Blount’s disease, Corrective osteotomy, Tibia vara, Transverse osteotomy.